anonymous
  • anonymous
Solve each equation for y. Then find the value of y for each value of x. 1. y+2x=5; x=-1, 0, 3 2. 5x=-4y+4; x=1, 2, 3
Mathematics
  • Stacey Warren - Expert brainly.com
Hey! We 've verified this expert answer for you, click below to unlock the details :)
SOLVED
At vero eos et accusamus et iusto odio dignissimos ducimus qui blanditiis praesentium voluptatum deleniti atque corrupti quos dolores et quas molestias excepturi sint occaecati cupiditate non provident, similique sunt in culpa qui officia deserunt mollitia animi, id est laborum et dolorum fuga. Et harum quidem rerum facilis est et expedita distinctio. Nam libero tempore, cum soluta nobis est eligendi optio cumque nihil impedit quo minus id quod maxime placeat facere possimus, omnis voluptas assumenda est, omnis dolor repellendus. Itaque earum rerum hic tenetur a sapiente delectus, ut aut reiciendis voluptatibus maiores alias consequatur aut perferendis doloribus asperiores repellat.
schrodinger
  • schrodinger
I got my questions answered at brainly.com in under 10 minutes. Go to brainly.com now for free help!
anonymous
  • anonymous
@texaschic101
anonymous
  • anonymous
please help me
texaschic101
  • texaschic101
1. y + 2x = 5 y = -2x + 5 <-- solved for y when x = -1 when x = 0 when x = 3 y = -2(-1) + 5 y = -2(0) + 5 y = -2(3) + 5 y = 2 + 5 y = 0 + 5 y = -6 + 5 y = 7 y = 5 y = -1 you understand how I did that one ??

Looking for something else?

Not the answer you are looking for? Search for more explanations.

More answers

anonymous
  • anonymous
yeah. you just plugged in the numbers for x to find y
texaschic101
  • texaschic101
exactly....but it is first asking you to solve for y.....although, even if you didn't solve for y, you could still sub in the x value into the original equation to find y
texaschic101
  • texaschic101
5x = -4y + 4 4y = -5x + 4 <-- this is solved for y now just sub in your x points....and find a numerical value for y
texaschic101
  • texaschic101
wait..messed up.. 4y = -5x + 4 y = -5/4x + 1 <--- this is the right one...sorry about that
texaschic101
  • texaschic101
y = -5/4x + 1 when x = 1 when x = 2 when x = 3 y = -5/4(1) + 1 y = -5/4(2) + 1 y = -5/4(3)+ 1 y = -5/4 + 1 y = -10/4 + 1 y = -15/4 + 1 y = -5/4 + 4/4 y = -10/4 + 4/4 y = -15/4 + 4/4 y = -1/4 y = -6/4 or - 3/2 y = - 11/4
anonymous
  • anonymous
thanks
texaschic101
  • texaschic101
sure thing :)

Looking for something else?

Not the answer you are looking for? Search for more explanations.